1980
DOI: 10.1126/science.6254154
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Peptide: A Possible Transmitter of Nonadrenergic Relaxation of Guinea Pig Airways

Abstract: Vasoactive intestinal peptide, a smooth-muscle relaxant neuropeptide with neurotransmitter properties, was relaxed during electrical field stimulation of guinea pig trachea. The amount released correlated with the degree of relaxation, and the release was blocked by tetrodotoxin. Prior incubation of the trachea with antiserum to vasoactive intestinal peptide reduced the relaxation. Thus vasoactive intestinal peptide may mediate the nonadrenergic relaxation of tracheal smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
96
3

Year Published

1987
1987
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(107 citation statements)
references
References 26 publications
8
96
3
Order By: Relevance
“…There is evidence supporting the existence of non-adrenergic, non-cholinergic (NANC) neurogenic regulation ofairway, (Matsuzaki et al, 1980;Cameron et al, 1983) genito-urinary (Snedden & Westfall, 1984 and cardiac smooth muscle (Saito et al, 1986) and NANC relaxation of coronary (Rooke et al, 1982) and other vessels (Duckles, 1979;Hamasaki et al, 1983) has been demonstrated. However, the identity of the neurotransmitters in this third nervous system are still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence supporting the existence of non-adrenergic, non-cholinergic (NANC) neurogenic regulation ofairway, (Matsuzaki et al, 1980;Cameron et al, 1983) genito-urinary (Snedden & Westfall, 1984 and cardiac smooth muscle (Saito et al, 1986) and NANC relaxation of coronary (Rooke et al, 1982) and other vessels (Duckles, 1979;Hamasaki et al, 1983) has been demonstrated. However, the identity of the neurotransmitters in this third nervous system are still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…pig (Matsuzaki et al, 1980) airway smooth muscle, a putative candidate is vasoactive intestinal peptide (VIP).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of cholinergic and sympathetic blockade, stimulation of vagal nerves, either by electrical current or via neural reflex pathways, elicits relaxation of preconstricted ASM cells via activation of iNANC pathways (2,12,17,56). Recent studies indicate that the iNANC system employs vasoactive intestinal peptide (VIP) (7,16,22,38,47,57), nitric oxide (NO) (4,30,36,44,51), or both (6, 14 -16, 64) to elicit ASM relaxation. However, the preganglionic origin of neurons containing these relaxing molecules has not been established.…”
mentioning
confidence: 99%
“…central nervous system control of the airways; parasympathetic preganglionic neurons; choline acetyl transferase; vasoactive intestinal peptide; nitric oxide synthase; nucleus ambiguus; airway constriction; airway dilation IN MANY SPECIES, INCLUDING HUMANS, airway smooth muscle (ASM) tone critically relies on the balance between central excitatory cholinergic control (3,19,33,49) and the inhibitory nonadrenergic, noncholinergic (iNANC) influences (2,12,17,47,56). Activation of cholinergic preganglionic neurons produces airway constriction, submucosal gland secretion and increased blood flow using acetylcholine as a neurotransmitter (23,25,26).…”
mentioning
confidence: 99%